Detroit - Simon Renoir (Communication)
Over the past decade, the city of Detroit has experienced a creative turnaround driven by the need to modernize and diversify the regional economy. This article looks at the role design has played in this process, and the factors that have established it as the central element of a strategy driving creativity in innovation and industrial and economic development. The author draws on institution documents and eight interviews conducted with local actors between September 2015 and September 2017.